Brazil - The Contrato Verde Amarelo Wage Subsidy : An Initial Assessment - Morgandi, Matteo; Fietz, Katharina; Ed, Malin (World Bank, Washington, DC, 2020)
In November 2019, the Brazilian government introduced, as part of an employment stimulus package, the Contrato Verde Amarelo (CVA), a wage subsidy program for young first-time employees entering in contracts of up to 1.5 minimum wages. Despite CVA did not pass the final senate vote and, consequently, lost its validity, the relevance of this measure remains in light of Brazil’s high labor costs and unemployment, and the dramatic impact that COVID-19 epidemic will leave in its labor market. This note analyzes the design, relevance and potential impacts of the CVA, as it was introduced in 2019, and recommendations for improvements based on international experience. In particular, as government will consider a revised version to speed up recovery of the labor market following COVID-19 epidemic, these recommendations will be useful in the drafting of an improved proposal.